El Programa Nacional de Formación y Capacitación Permanente (Pronafcap) - Rodríguez Manrique, Catherine Paola (2010)
This article describes the main characteristics of the Teacher Training National Program that is leading by the Peruvian government since 2007 addresses to basic education teachers. Previous public training programs to teachers have mentioned as backgrounds of the present Program. In addition the author focuses on the political, pedagogy, economics, and assessment dimensions of the Program.